Domestic Public Opinion in Civil War Negotiations: Analysis of the Sri Lankan Experience - Waradas, Thiyagaraja (University of Colombo, 2015)
Why civil war negotiations fail and conflicts recur, is the central question in conflict negotiation literature. However, the role played by ideological factors, in particular Domestic Public Opinion (DPO) is under-theorized in the civil war negotiation literature. Thus, this study, attempts to address the gap by seeking to answer the following question: why do warring parties display more conciliatory negotiation behavior in certain negotiations and not in other negotiations in the context of civil war? The aim of this research is to explain the relationship between DPO and the negotiation behavior of the government. By doing so, the study aims to offer an insider's view on negotiation and to address a methodological lacuna by providing non-institutionalized indicators derived from its empirical analysis. The study employs a comparative case study approach with structured focused comparison methods to examine negotiations in the Sri Lankan conflict. The two negotiation efforts are namely, Wickremasinghe- LTTE negotiations in 2002-2003 and Rajapakse-LTTE negotiation in 2006. Public opinion surveys, government positions and conduct have been used to operationalize the DPO and negotiation behavior of the government.
Keywords: Domestic Public Opinion, Civil war, Negotiations, LTTE, GoSL